Assessing noise emission levels from earthwork construction equipment - Haron, Zaiton (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2012)
Noise emission levels from construction equipment are an important factor in the determination of the level of noise exposure of construction workers and the neighbourhood. This paper presents: (1) an investigation of the noise emission levels generated from typical earthwork construction equipment, that is, excavators and compactors; (2) a comparison between the noise emission level obtained from local equipment and the noise emission level given by the United Kingdom standard BS5228:2009. Noise emission levels of 50 excavators and 25 compactors with various power levels and ages were obtained from on-site measurements. About 74% and 48% of the excavators measured in this study were shown to have noise emission levels below the limits specified by the Department of Environment (DOE) Malaysia and European Directive 2005/88/EC respectively, while 52% of compactors achieved levels below the EC limits. There is also a strong relationship between the mean sound pressure level and the age factor but an insignificant relationship with increases in net installed power. A comparison of measured data with BS5228 data indicated that statistically only new data in BS5228:2009 have insignificant differences from measured data. With these results new data in BS5228:2009 can be used with confidence by environmental impact assessment (EIA) practitioners during the prediction of noise at the planning stage.